(untitled) (International Journal of Physiotherapy, 2020)
Background: The Anterior Cruciate Ligament (ACL) injury is the most traumatic knee joint injury. Surgical reconstruction is the common standard treatment care to ensure an early functional gain. Active quadriceps exercises were introduced at early rehabilitation to prevent muscle lag. However, patients’ pain, muscle compensation from other parts of the body, and rapid development of quadriceps weakness were factors that slow down the positive progression of post ACL rehabilitation. Therefore, a new exercise instrument is needed to facilitate muscle contraction during post ACL reconstruction exercise actively. The Myo-Tech is an instrument that helps the patient contract correct muscle during the early phase of rehabilitation. The purpose of this study is to investigate the reliability of the Myo-Tech instrument measuring quadriceps contraction on post ACL reconstruction. Methods: This is a cross-sectional study design and was carried out on patients with post ACL reconstruction. The patients were required to perform static Quadriceps exercises (SQE) for 10 seconds with Myo-Tech strapped at the upper thigh around the quadriceps area. Graph of muscle contraction was measured for the highest and lowest value in the 10 seconds. Results: A total of 29 male subjects were involved in this study. The reliability of Myo Tech assist patients in quadriceps contraction is good (r = 0.67). Conclusion: This study showed that Myo Tech is a promising instrument and can be integrated into clinical practice. The Myo-Tech can be used as an assessment tool to determine proprioceptive deficits following muscle weakness.